KNOWLEDGE AND ATTITUDES TOWARD SINGLE-USE PLASTIC PRODUCTS AND ASSOCIATED FACTORS: A CROSS-SECTIONAL STUDY IN O MON WARD, CAN THO CITY (Vietnam Journal of Community Medicine, 2026)
Objective: To assess knowledge and attitudes toward single-use plastic products and to identify associated factors among community residents in O Mon ward.Subject and method: A cross-sectional study was conducted among adults aged 18 years and older using structured questionnaires from December 2022 to December 2023. Descriptive statistics and logistic regression analyses were applied to identify factors associated with knowledge and attitudes.Results: Among participants, 61.1% demonstrated adequate knowledge and 57.0% showed positive attitudes toward reducing single-use plastic use. Households without children under five years of age were more likely to have adequate knowledge (OR=0.51; p=0.007). Kinh ethnicity and households with pregnant women were significantly associated with positive attitudes (OR=2.02; p=0.02; OR=0.13; p=0.02). Knowledge was strongly associated with attitudes, with participants who had adequate knowledge being 5.27 times more likely to report positive attitudes compared with those with inadequate knowledge (p
Keywords: knowledge, attitude, single-use plastics